Assessment of quantitative relationship between blood and PRF for periodontal surgeries - Indurkar, Maya S; Bhailume, Pallavi Sunil (International Journal of Dental Research, 2017)
Aim: The aim of study is to measure the amount of PRF obtained from different quantity of blood withdrawn from patients & the amount of PRF and its use in different periodontal surgical procedures.Materials and method: 15 subjects undergoing regenerative periodontal surgical therapy in whom use of PRF was indicated were included in the study. 15 subjects were divided into 3 three groups. In group A: 5ml of blood was withdrawn from 5 subjects. In group B: 10ml of blood was withdrawn from 5 subjects. In group C: 12ml of blood was withdrawn from 5 subjects. The steps involved were as follows:1) Blood specimen was withdrawn from the patient,2) The blood specimen was immediately placed in the centrifuge and was allowed to spin for 10mintes at 3000RPM,Weight of obtained PRF was measured by using weighing scale and also length, depth & width was measured by using UNC 15 probe.Result and Conclusion: The amount of PRF obtained depends upon the quantity of blood withdrawn. Thus, result of the present study is helpful to the operator to decide the quantity of blood to be withdrawn for particular patient to obtain desired amount of PRF.